SUMBERDAYAMANUSIAINDONESIA MENGHADAPI ERA GLOBALISASI EKONOMI DITINJAU DARI SEGI PEMERATAAN - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2009)
MostIndonesianswouldagreethattheIndonesianenterprisesshoulddefinitely playamoreefficientroleinthe globaleconomy.However,the argumentthat insistonthequalityofhumanresources.Evenifthegovernmentwas willingto committoacomprehensive programs. .Whileattempttoimprove educationalprogramsthroughinternalrestructuringmay bea validconcept. Thepresent culturein governmentmeans itis toimplementreformssuccessfully.Thewillingnessandthecapacitytoapproachthecapacityofhumanresourcesforchangetoface_gneconomicalglobalproblems